MiR-223 inhibits hyperosmolarity-induced inflammation through downregulating NLRP3 activation in human corneal epithelial cells and dry eye patients. (July 2022) - Ren, Yueping; Feng, Jiayao; Lin, Yi; Reinach, Peter S.; Liu, Youjia; Xia, Xiaoyu; Ma, Xiaoyin; Chen, Wei; Zheng, Qinxiang
Abstract: We previously showed that increases in reactive oxygen species (ROS) generation upregulate NLRP3 inflammasome and inflammation through increases in both caspase-1 activity and rises in IL-1β expression levels in animal models of dry eye (DE). As changes in microRNA (miRNAs) expression levels can modulate inflammasome function, we determine here if there is a relationship in DE between changes in miR-223 expression levels and NLRP3 activation induced in an intelligent controlled environmental system (ICES) in mice. In parallel, ROS, miR-223 and NLRP3 expression levels were assessed in conjunctival impression cytology and tear fluid samples obtained from DE patients and normal subjects. MiR-223 expression levels were modulated by transfection of either a mimic or its negative control (NC) in a human corneal epithelial cell line (HCECs) exposed to a 500 mOsm hyperosmotic medium for 4 h. The dual-luciferase reporter assay confirmed that miR-223 controls NLRP3 gene expression readout through directly interacting with the 3' UTR of its mRNA. Hyperosmolarity-induced NLRP3 activation was confirmed based on recruitment and colocalization of NLRP3 with ASC as well as increases in IL-1β expression. The miR-223 expression level decreased by 55% in the conjunctiva and cornea of the murine DE model from the level in the control group (P ≤ 0.047), while NLRP3 protein expression rose by 30% (P ≤ 0.017). In DE patients, miR-223 expression decreased in conjunctival impression cytology samples (P = 0.002), whereas IL-1β tear content rose significantly (P < 0.001).The relevance of this decline was confirmed by showing that exposure to a 500 mOsm stress decreased the miR-223 expression level whereas ROS generation as well as the NLRP3, and IL-1β expression levels rose in HCECs (P ≤ 0.037). In contrast, miR-223 mimic transfection reduced the NLRP3 protein expression level by 30% (P = 0.037), whereas both ROS generation and IL-1β secretion rose compared to their corresponding levels in the control group (P ≤ 0.043). Thus, miR-223 negatively regulates NLRP3 inflammasome activity via suppressing NLRP3 translation in DE. This inverse regulation between miR-223 and NLRP3 expression levels suggests that selective upregulation of miR-223 expression may be a novel option to suppress chronic inflammation in DE. Highlights: MiR-223 negatively regulates DE inflammation through suppressing NLRP3 activation. Conjunctival miR-223 expression declines and tear IL-1β level rises in DE patients. Stimulation of miR-223 expression provides an option to alleviate DE inflammation.